Life satisfaction of adopted and non-adopted adolescents in four European countries - Laura Ferrari; Emanuele Koumantakis; Sonia Ranieri; Lorena Charrier; Maite Román; Isabel Cáceres; Laurie C. Miller; Carmen Moreno; Francisco Rivera; Paola Berchialla; Rosanna I. Comoretto; Pablo Carrera; et al. (Scientific Reports)
Abstract Adoptees, a group of children consistently shown to be at higher risk of psychosocial difficulties, face particular challenges during adolescence. However, few studies address the well-being of adopted adolescents, and cross-cultural comparisons are rarely reported. The present study assessed the life satisfaction of internationally adopted and non-adopted adolescents living in four European countries. An overall sample of 776 adolescents completed self-report questionnaires. Descriptive analysis and logistic regression models were performed to investigate the association between adoption status and life satisfaction. Adoptees were found at higher risk for low life satisfaction across countries compared to their non-adopted peers (OR = 5.73, 95%CI 2.70-12.16). Friend support was a protective factor, while poor communication with parents was a risk factor for low life satisfaction in both groups. Our findings highlighted the importance of promoting family and social relationships to support the well-being of adopted and non-adopted adolescents in diverse European countries.